Forecasting ticket demand for the Super Bowl - Venkataraman, Ray R.; Pinto, Jeffrey K. (Los Angeles, CA : SAGE Publications, Inc., 2017)
This case examines causes of an unanticipated rise in prices of the 2015 Super Bowl tickets to highlight challenges in demand forecasting. To accurately predict ticket demand for the 2015 Super Bowl, the forecast needs to take into account a broader ticketing supply chain. The skyrocketing escalation of ticket prices up to Super Bowl Sunday (no tickets for less than $9,000) left average sports fans without tickets and many ticket brokers in the secondary market with losses. The challenges of demand forecasting are clearly demonstrated.
Originally published in Venkataraman, R. R., & Pinto, J. K. (2017). Forecasting ticket demand for the Super Bowl. In Operations management: Managing global supply chains (pp. 496-497). Thousand Oaks, CA: SAGE Publications. ISBN: 9781506302935.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Ticket brokerage -- United States -- Case studies